STRATEGIC HR REDEFINITION, HR MANAGEMENT INITIATIVES RESPONDING TO THE CHALLENGES OF THE NEW NORMAL ERA - Zukra Budi Utama; Rinaldi Rustam (Lembaga Penerbit Fakultas EKonomi dan Bisnis, 2022)
The COVID-19 pandemic declared by UNDP has an impact on the global economic crisis, according to the ERC, which is more detrimental to small and medium enterprises than large companies. This is a classic problem that is fundamental to HR management, regarding the need for a fundamental redefinition of the function and role of HR in terms of social responsibility. It is necessary to increase the capacity of human resources in different ways, towards capabilities without theoretical limits, realizing the contribution of human resources that has unlimited impact, not only in the organization but also in the social sphere of society. Our experiments increased the capabilities of more than 500 workers, proving that in less than a month they were able to identify problems in their fields that had not been seen so far, an average of 40% to 70% of implementation standards, and were able to increase innovation in organizations up to two hundred times (20,000%) in a year. From here we identify the element of feeling that we call intuition as a human advantage that is able to support it in greater achievements Natural HR as the future strategic HR is the answer of HR Management entering a new era, as a redefinition of the function and role of HR. For that we make improvements with the BCGC model or the zukra model.